The negative impact of anthropogenic factors on the state of groundwater of Kazakhstan - Osipov, S.; Yermenbai, A.; Akylbekova, A.; Livinsky, Y.; Anarbekov, Oyture (National Academy of Sciences of the Republic of Kazakshtan, 2020)
This article reviews the negative impact of anthropogenic changes on groundwater. The main changes in physical and geographical conditions that occur under the impact of anthropogenic pressures and that have the most significant influence on the state of groundwater, as well as a negative impaction the conditions of the formation of groundwater are: changes in the landscape caused by agricultural works, mining, construction of settlements, etc.; changes in the hydrographic network caused the construction of hydroelectric power facilities; changes in the composition of the atmospheric air; changes in the groundwater level regime, climatic conditions. The most significant factor of change in groundwater formation conditions is the progressive anthropogenic pollution of groundwater. It negatively influences the number of resources and their quality.